Hans Sloane, the reinvention of the museum, and the promotion of Christian knowledge - Craske, Matthew (The journal of religious history, literature and culture, 2024)
This article argues that Hans Sloane conceived of museums as an aspect of what the laity could achieve in the field of promoting Christian knowledge. This was considered, upon Lockean terms, as being founded in reason. Sloane’s scientific endeavours were, like Robert Boyle before him, an effort towards rebuilding the nation upon a shared vision of a ‘natural’ faith. This example is contrasted with a spoof museum closely associated with Sloane’s circle, Don Saltero’s Coffee House, which was founded upon a lampoon of a Catholic reliquary and satirised the concept of the cabinet of curiosities. This argument runs counter to prevailing views of museums as post-Enlightenment institutions intended to oppose the role of faith in society and replace them with secular alternatives.